Policía beyond the police - Gutiérrez, Laura (Theoretical criminology, 2023)
This article develops and extends the critical theory of police power by applying it to Colombia. Scholarship on police in Colombia has been undermined by a focus on the kind of creation myth that one finds in most histories of police: that policing only properly begins in a key foundational year. In Colombia, that year is 1891. This approach overlooks or downplays the importance of the concept of policía. This is the original and far more expansive police concept through which social order in Colombia was fabricated. By paying attention to the continued importance of policía, this article drastically transforms our understanding of police power and state formation in Colombia, and extends the critical theory of police power.